ANALISIS STRATEGI BISNIS UNTUK MEMPERTAHANKAN DAYA SAING PADA AGEN PERJALANAN WISATA DITINJAU DALAM PERSPEKTIF BISNIS ISLAM STUDI PADA YURA TRIPS LAMPUNG - Fatih Fuadi; Deni Saputra (CV SWA Anugrah, 2024)
Purpose: The purpose of this research was conducted in order to be able to find out business strategies, factors that influence competitiveness, as well as business strategies from an Islamic business perspective at the Yura Trips Lampung travel agent.Research methodology: The research method used in this research is field research. Field research is research using field data collection techniques such as observation, interviews, distribution of questionnaires, which will become a source of research information. This research will be taken from the results of interviews in the field and observations. Apart from that, this research will also take data from books, as well as the results of previous research and all data related to the research theme.Results: As a result of the research that researchers have conducted, it can be seen that there are several business strategies to maintain the competitiveness of the Yura Trips Lampung travel agent. Yura Trips Lampung is a travel services company that helps tourists to obtain information and tourist needs. Yura Trips Lampung realizes the importance of benefiting the wider community, especially the local community in the tourist area. Therefore, several of the Yura Trips team are local residents whose aim is for local residents to experience the sweet world of tourism and also increase employment opportunities thereby reducing the number of unemployed. Yura Trips Lampung pays attention to ideal business ethics so that it does not harm either party or both, in which case Islam always prioritizes the principles of justice and balance of rights and obligations in every business activity.Limitations: The drawbacks of this research are the limited time in searching for primary data in this study, and also the limitations of the place in conducting this research, the place for conducting this research is only done in one place.Contribution: The results obtained through this research can be used as material for consideration by Travel Agents in making decisions and can also be used as a reference for further research.